Between exile and memory: Victorina Durán, a 20th-century Spanish lesbian artist - Cristina del Águila (2i Revista de Estudos de Identidade e Intermedialidade)
This article aims to compile the various aspects of the life and work of Victorina Durán (Madrid, 1899 - Madrid, 1993), a Spanish artist whose artistic production remained largely overlooked until recently. Throughout the following pages, we will analyze, from an intersectional feminist perspective, both her personal and artistic trajectories, marked by her exile to Buenos Aires following the Spanish Civil War and her subsequent return to Spain. We will pay particular attention to her unapologetic homosexuality and the survival strategies she employed to maintain her artistic practice in adverse contexts. The article concludes by advocating for the importance of recovering the memory of artists like Victorina Durán, whose work and experiences offer a valuable contribution to our understanding of 20th-century Spanish art and the compilation of testimonies of LGTBIQ+ artists.